Reconstruction of virtual neural circuits in an insect brain - Namiki, Shigehiro; Haupt, Shuichi S.; Kazawa, Tomoki; Takashima, Akira; Ikeno, Hidetoshi; Kanzaki, Ryohei (Frontiers in Neuroscience, 2009)
The reconstruction of large-scale nervous systems represents a major scientific and engineering challenge in current neuroscience research that needs to be resolved in order to understand the emergent properties of such systems. We focus on insect nervous systems because they represent a good compromise between architectural simplicity and the ability to generate a rich behavioral repertoire. In insects, several sensory maps have been reconstructed so far. We provide an overview over this work including our reconstruction of population activity in the primary olfactory network, the antennal lobe. Our reconstruction approach, that also provides functional connectivity data, will be refined and extended to allow the building of larger scale neural circuits up to entire insect brains, from sensory input to motor output.